CTX‐M‐15‐producing Morganella morganii from Hôpital Principal de Dakar, Senegal. Issue 2 (20th March 2014) - Diene, S. M.; Fenollar, F.; Fall, B.; Sow, K.; Niang, B.; Samba Ba, P.; Wade, B.; Raoult, D.; Rolain, J.‐M.
Abstract We report the detection and molecular characterization of extended spectrum β‐lactamases in a series of 112 clinical isolates of Enterobacteriaceae from the Hôpital Principal de Dakar, Senegal, including five CTX‐M‐15‐producing Morganella morganii isolates, which are reported for the first time in this country.